Instability of U3Si2 in pressurized water media at elevated temperatures - Artaches Migdisov (Nature Portfolio, 2021)
Uranium silicide is proposed as a highly accident tolerant light water reactor nuclear fuel, but its behavior under high-temperature, aqueous conditions is poorly studied. Here, uranium silicide is shown to decompose and fully oxidize when the passive uranium silicate layer is destabilized under hydrothermal conditions over 300 °C.